The Reproduction and Life Cycle of a South African Population of Xiphinema index - Malan, A.P.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
The seasonal fluctuation of a South African Xiphinema index population, the influence of four hosts on the length of the life cycle and the reproductive rate with fig as host at three different temperatures, were studied. Reproduction was highest during early summer (November and December ) when the mean maximum dayly air temperature was between 25 and 30°C. Under controlled conditions at 25±2°C the duration of the life cycle of X. index was between 75 and 85 days with the grapevine rootstock Fairy as host, between 55 and 65 days with Jacquez rootstock and between 45 and 55 days with fig and Paulsen 775 rootstock. Using fig as host, the highest reproductive rate of the nematode was at 28°C, with a 216-fold increase and the lowest at l8°C, with no adults after 85 days.